Wrist/forearm passive exoskeleton for adding tuneable mechanical damping impedance - Teo, Jiunntian. (2011)
Assessing how humans adapt to environment dynamics has provided fundamental cues to better understand motor control and learning in humans. To this end, robots have often been used to produce pre-programmable force fields, e.g. for the generation of elastic and/or viscous field. Despite the high degree of back-drivability, state-of-the-art robots used in rehabilitation have been shown to perturb natural sensorimotor strategies in redundant tasks. This project aims at developing passive device for the production of viscous force field for the wrist movements. The project started from lightweight exoskeleton devices which were known not to perturb human sensorimotor strategies and incrementally (initially passive) add elements such as mechanical dampers to generate viscous fields. The programmability features were achieved mechanically, e.g. via manual adjustments. All devices, after proper characterization, were tested experimentally in relation to their effect on sensorimotor strategies during pointing tasks.